Communication Policy Of The Ministry Of Religious Affairs Of The Republic Of Indonesia In Socializing The Onh Increase And Its Implications For Prospective Pilgrims In Medan City - Siregar, Alya Rahmayani; Mailin, Mailin; Ritonga, Hasnun Jauhari (UNIVERSITAS PAKUAN, 2023)
The purpose of this research is to analyze RI's policy communication in socializing the increase in the cost of Hajj and its implications for prospective pilgrims in Medan city. The research method that researchers use is a qualitative approach because it is considered appropriate to use in this study. Qualitative research is defined as an investigative process to understand social problems based on the creation of a complete holistic picture formed with words, reporting the views of informants in detail, and arranged in a background. Policy communication is carried out by providing information through activities such as workshops and FGDs to the Hajj pilgrimage guidance groups. Some prospective pilgrims are a little heavy to accept this policy, but from those who accept it fully related to the newly passed policy, also hope that it will not be the wrong policy in the future.